(untitled) (Research, Society and Development, 2019)
In the citizen Constitution of 1988, and in the principles and social contexts tied to it, the searching for attenuation of social differencies has special focal point, including in this consideration the list of protection to the disabled person. Thirty years after its promulgation, there is, on the one hand, advance in wich concers to estructural alterations of acessability, and on the other, Strong critics on the inattention to inclusion of more extensive tipical. Under that perspective, the present article will demonstrate the need of recognition on the extension of rights to the disabled person, to reach na effective inclusion policy that will allow a way out of the state of absolute realiance. Trough the decdutive method and the interdisciplinar bibliographic review, interpretating the final goal of the juridical norm, it is analysed the safeguard to the capacity of the disabled person, without damaging it’s liberty, concluding that remains impossible the real insertion if the legal perspective reduces it’s rights to mere subsistance.